(untitled) (Journal of Geography and Environmental Management, 2019)
This article discusses and psevdokarstovye karst processes in the territory of West Kazakhstan region associated with salt dome tectonics of the Caspian Basin. The studies identified three areas with failures neoplasms suffusion origin. Funneling mechanism associated with the unloading and post-salt horizons offset limestone eluvium under the influence of erosion and denudation processes.